2020
DOI: 10.3390/admsci10030068
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nationality and Hotel Class on Guests’ Satisfaction. A Fuzzy-TOPSIS Approach Applied in Saint Petersburg

Abstract: Although hotels usually have clients from different nationalities, the research analyses the multicultural effects on hotel customers’ satisfaction is still scant. This paper aims to contribute to the realm of hotel management by providing interesting managerial insights into how different nationalities perceive hotel attributes differently using two hotels located in Saint Petersburg as a case study. To that end, a fuzzy hybrid method based on the technique of similarity to ideal solution (FTOPSIS) is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…The methodology is derived from a hybrid approach based on Fuzzy Set Theory (FST) and techniques for order preference by similarity of the ideal solution (TOPSIS). TOPSIS techniques are considered appropriate tools to handle different decision-making processes and they are especially attractive when respondents make choices with multiple attributes in consideration [52]. Moreover, the essence of the human ambiguity judgement when dealing with multidimensional attributes can be captured by fuzzy methods [53], which is an important task when using Likert scales based on linguistic terms.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology is derived from a hybrid approach based on Fuzzy Set Theory (FST) and techniques for order preference by similarity of the ideal solution (TOPSIS). TOPSIS techniques are considered appropriate tools to handle different decision-making processes and they are especially attractive when respondents make choices with multiple attributes in consideration [52]. Moreover, the essence of the human ambiguity judgement when dealing with multidimensional attributes can be captured by fuzzy methods [53], which is an important task when using Likert scales based on linguistic terms.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Radojevic et al (2018) suggested that hotel star classification significantly influences CS, with higher-rated hotels often contributing to overall CS with their hotel services. Martín et al (2020) stated that luxury hotels typically have a more uniform level of CS, while middle-or low-class hotels typically have more diverse opinions. Furthermore, the star-rating system is commonly used to assess the quality of hotels, with guests of four-and five-star establishments generally having higher expectations for hospitality and service (Moreno-Perdigon, Guzman-Perez & Mesa, 2021).…”
Section: Differences In Customer Satisfaction Based On Demographic An...mentioning
confidence: 99%
“…Furthermore, Martín et al (2020) mentioned that there are significant differences in guest behavior between different cultures. Ozdemir et al (2012) provide evidence that nationality is an effective variable for revisiting intentions among tourists.…”
Section: Differences In Repurchase Intentions Based On Demographic An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The relative weight of the affective antecedents on perceived value and satisfaction is significant (Gallarza et al 2013), because these factors influence consumers' behaviors, including their repurchase intentions (Ali et al 2016). Perceived satisfaction affects the willingness of visitors to revisit a destination according to their own place of origin (Bonera et al 2017;Martín et al 2020). Therefore, tourism service providers need to pay attention to the factors that form the satisfaction of visitors, so that they may meet them to the highest possible extent.…”
Section: Literature Reviewmentioning
confidence: 99%